Sara Mills Model Critical Discourse Analysis on the Peaky Blinders Serial - Evira Ayustin; Maylanny Christin (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The research entitled Critical Discourse Analysis of Sara Mills Model in Peaky Blinders Serial (Case Study of Gender in Audio Visual Media) was conducted on the object of research in the form of audiovisual media as part of the communication media. This study seeks to examine gender issues in the form of discrimination against women which is shown in the Peaky Blinders series which is a text. Peaky Blinders is a drama series from England which is currently finished until season 6 breaths of air on the BBC and Netflix. The drama series was directed by Otto Brust with the main character Cillian Murphy. The researcher conducted this research based on the dominance of patriarchal culture and the series Peaky Blinders which is a crime drama genre featuring several scenes of resistance to patriarchal culture performed by several female characters. Researchers conducted research using a critical discourse analysis approach Sara Mills model. Sara Mills' discourse analysis model is often known as feminist stylistic in linguistic studies because it focuses on examining women's discourse from the perspective of feminism. Sara Mills' approach focuses on the position of the actor in a text which in this study is a film. Based on the critical discourse analysis of the Sara Mills model, the researcher conducted a study of the Peaky Blinders series by dividing it into discrimination against women in the position of the subject (who tells the story), discrimination against women in the position of the object (which is told), and discrimination against women in the position of the audience. In addition, researchers also provide identification of forms of discrimination against women shown in the Peaky Blinders series. The research was conducted by observing the Peaky Blinders series and then reducing the data in the form of a set of scenes to scenes to facilitate research, presenting data with tables, and conclusion drawings with narrative descriptions of the data displayed, then analyzed using triangulation of data sources.